Application of response surface methodology for optimization of urea grafted multiwalled carbon nanotubes in enhancing nitrogen use efficiency and nitrogen uptake by paddy plants - Mohd Yatim, Norazlina; Shaaban, Azizah; Dimin, Mohd Fairuz; Yusof, Faridah; Abdul Razak, Jeefferie (Hindawi Publishing Corporation, 2016)
Efficient use of urea fertilizer (UF) as important nitrogen (N) source in the world's rice production has been a concern. Carbon-based materials developed to improve UF performance still represent a great challenge to be formulated for plant nutrition. Advanced N nanocarrier is developed based on functionalized multiwall carbon nanotubes (f-MWCNTs) grafted with UF to produce urea-multiwall carbon nanotubes (UF-MWCNTs) for enhancing the nitrogen uptake (NU) and use efficiency (NUE). The grafted N can be absorbed and utilized by rice efficiently to overcome the N loss from soil-plant systems. The individual and interaction effect between the specified factors of f-MWCNTs amount (0.10-0.60 wt%) and functionalization reflux time (12-24 hrs) with the corresponding responses (NUE, NU) were structured via the Response Surface Methodology (RSM) based on five-level CCD. The UF-MWCNTs with optimized 0.5 wt% f-MWCNTs treated at 21 hrs reflux time achieve tremendous NUE up to 96% and NU at 1180 mg/pot. Significant model terms (p value < 0.05) for NUE and NU responses were confirmed by the ANOVA. Homogeneous dispersion of UF-MWCNTs was observed via FESEM and TEM. The chemical changes were monitored by FT-IR and Raman spectroscopy. Hence, this UF-MWCNTs' approach provides a promising strategy in enhancing plant nutrition for rice.